Automatic Imitation in Comorbid PTSD & Alcohol Use Disorder and Controls: an RCT of Intranasal Oxytocin. (October 2020) - Morrison, Tyler E.; De Coster, Lize; Stauffer, Christopher S.; Wen, Jin; Ahmadi, Elnaz; Delucchi, Kevin; O'Donovan, Aoife; Woolley, Josh
Highlights: Higher automatic imitation in co-morbid PTSD and alcohol use disorder (PTSD-AUD) than controls. Oxytocin administration increased automatic imitation in controls, replicating prior findings. Oxytocin administration did not increase automatic imitation in the PTSD-AUD group. Abstract: Introduction: Mimicking movements of others makes both the imitating and imitated partners feel closer. Oxytocin may increase focus on others and has been shown to increase automatic imitation in healthy controls (HC). However, this has not been replicated, and oxytocin's effects on automatic imitation have not been demonstrated in clinical populations. This study attempts to replicate effects on HC and examine effects on people with comorbid posttraumatic stress disorder and alcohol use disorder (PTSD-AUD). Methods: Fifty-four males with PTSD-AUD and 43 male HC received three intranasal treatment conditions (placebo, oxytocin 20 International Units (IU), and oxytocin 40 IU) in a randomized order, across three separate testing days, as part of a double-blind, crossover parent study. At 135 min post-administration, each performed the imitation-inhibition task, which quantifies automatic imitation as the congruency effect (CE). After exclusions, the final analyzed data set included 49 participants with PTSD-AUD and 38 HC. Results: In HC, oxytocin 20 IU demonstrated a statistically significant increase in CE, and 40 IU showed a trend-level increase. In PTSD-AUD, oxytocin did not significantly increase CE. Post-hoc analysis showed the PTSD-AUD group had higher CE than HC on placebo visits. Discussion: Our data suggest PTSD-AUD is associated with higher automatic imitation than HC in the absence of oxytocin administration. We successfully replicated findings that oxytocin increases automatic imitation in HC. This demonstrates an unconscious motor effect induced by oxytocin, likely relevant to more complex forms of imitative movements, which have the potential to improve social connection. We did not find a significant effect of oxytocin on automatic imitation in PTSD-AUD. Future research should examine imitation in both sexes, at peak oxytocin levels, and on increasingly complex forms of imitation.